Femininities and masculinities in highly skilled migration: Peruvian graduates’ narratives of employment transitions and binational marriages in Switzerland - Seminario, Romina (Migration Letters, 2018)
Biographic research about migrant’s gender identities grasps tendencies of normativity change chronologically and transnationally. Transition to employment stories of Peruvian graduates from Swiss universities evoke continuities and changes in femininities and masculinities from Peru to Switzerland. Binational marriages that mediate employment transition after graduation play an ambivalent role in the attainment of jobs commensurate to skills. Career, partner, and care are key elements of transgressing and reinforcing non/hegemonic masculinities and un/desirable femininities from super scientist women to failing male breadwinners. Feminization of highly skilled migration from Peru is linked to urban middle classes where femininities are increasingly based on career advancement. However, these professional-oriented femininities might be neutralized in favour of care-oriented femininities from family models in Switzerland. While Peruvian female graduates constructed an ideal of care/career integration predominantly, male counterparts emphasized the risk of career success at the expense of partnership.